Legal Protection Against Notaries Due to Interceptors Who Provide False Information in the Minuta of the Deed of Sale and Purchase (Study of High Court Decision Number 99/PID/2020/PT. BDG) - Revina Destiani Putri; Mohamad Fajri Mekka Putra (LEGAL BRIEF, 2022)
The notary in carrying out his office has the authority to make authentic deeds by listening to the will of the parties to be contended into a deed. Authentic deeds have the function of being perfect evidence regarding the information and facts contained therein. However, in practice, problems often arise where the presenter gives false information to the notary. This is certainly detrimental to the notary and has a legal impact regarding the proof of authentic deeds made by the notary. The purpose of writing this journal is to analyze the legal protection of notaries who are harmed due to false information provided by the interceptor. The method used in writing scientific journals is normative juridical, namely literature law research by examining literature materials or secondary data.